The Influence of Social Media Addiction on Academic Engagement with Self-Esteem Mediation in Students - Dewi, Adinda Rasita; Rejeki, Asri (World Psychology, 2025)
Amid concerns over declining academic performance, as indicated by metrics like PISA scores, student academic engagement has become a critical issue. The proliferation of digital technology has introduced new challenges, with social media addiction emerging as a significant potential detriment to students’ focus and motivation. Concurrently, psychological factors such as self-esteem are crucial in shaping students’ academic attitudes and behaviors. This study aims to determine the influence of social media addiction on the academic engagement of high school students, and to examine the mediating role of self-esteem in this relationship. A quantitative research design using a survey method was employed. The sample consisted of 146 high school students selected through purposive sampling. Data were collected using three validated instruments: the Utrecht Work Engagement Scale-Student Survey (UWES-SS) for academic engagement, a scale adapted from the Young Internet Addiction Test for social media addiction, and the Rosenberg Self-Esteem Scale. Data were analyzed using multiple regression analysis. The findings revealed a significant negative influence of social media addiction on academic engagement (p < 0.05). Conversely, self-esteem was found to have a significant positive influence on academic engagement (p < 0.05). The simultaneous analysis confirmed that social media addiction and self-esteem together have a significant effect on students’ academic engagement.